Datopotamab deruxtecan induces hallmarks of immunogenic cell death - Sabrina Forveille; Marion Leduc; Allan Sauvat; Guido Kroemer; Oliver Kepp (Cell Stress)
Antibody-drug conjugates (ADCs) offer a strategy for targeted delivery of cytotoxic agents to cancer cells. In this study, we investigated the mechanism of action of datopotamab deruxtecan, an ADC composed of a monoclonal antibody targeting tumor-associated calcium signal transducer 2 (TACSTD2, also known as trophoblast cell-surface antigen-2 (TROP2)) conjugated to the topoisomerase I inhibitor DXd. Datopotamab deruxtecan reduced the viability of human osteosarcoma U2OS cells engineered to express TROP2, but had no effect on their parental counterparts, which only expressed the CALR-GFP biosensor. In TROP2-expressing cells, it triggered the translocation of CALR-GFP from the ER to the cell periphery. Both datopotamab deruxtecan and its DXd payload elicited several features characteristic of immunogenic cell death (ICD), including detectable calreticulin exposure on the cell surface, release of high-mobility group box 1 (HMGB1), and ATP secretion into the culture medium. Importantly, the TROP2-targeted ADC also exerted a bystander antitumor effect on parental U2OS cells (lacking TROP2 expression) co-cultured with TROP2-expressing U2OS cells. These findings demonstrate that datopotamab deruxtecan delivers a cytotoxic payload capable of inducing hallmark features of ICD in vitro.